Project manager's spotlight on change management - Baca, Claudia (Harbor Light Press, 2005)
Clear-Cut Ways to Manage Inevitable Project Changes. If you're a typical project manager, you're probably aware of the importance of change management but may not have the time or expertise to develop a full-blown plan. Here's a quick and practical guide to applying the disciplines of proven change management practices without the rigor of complex processes.